Clinical characterization of anophthalmic and microphthalmic cavities in individuals with craniofacial anomalies - Paula, Isabella de Oliveira Lima Parizotto (2022)
Objective: Measure the frequency of anophthalmic and microphthalmic patients with craniofacial anomalies (FCAs). Design Descriptive, cross-sectional, retrospective study.Setting Hospital for Rehabilitation in Craniofacial Anomalies of the University of São Paulo (HRAC-USP, Bauru, São Paulo, Brazil). Patients The medical records of patients treated at HRAC from 2000 to 2012 with a diagnosis of anophthalmia or congenital microphthalmia were examined. Patients were excluded for secondary anophthalmia, incomplete medical records, or information that could not be accessed. Outcome Measures Frequency of anophthalmia and microphthalmia; the proportions and diagnoses of associated FCAs; impairment of ocular appendages; extracranial or facial anomalies; genetic alterations; and surgical approach. Results A total of 56 patients had anophthalmia (52.3%), 35 had microphthalmia (32.7%), and 16 patients had both (15%). Individuals with FCAs associated with microphthalmia, anophthalmia, or both totaled 74, corresponding to 69.2%. Anophthalmia was more likely than microphthalmia to be accompanied by FCAs, at 76.4% of patients (p < 0.05). Cleft lip and palate were the main malformations associated with anophthalmia (23.64%), with microphthalmia (45%), and with both (44.44%). Reconstructive surgery was done in 63.6% of cases. The ocular attachments were compromised in 71% of cases. Extracraniofacial malformations were found in 9.3% of patients. Only seven records contained karyotypes, and no changes directly related to anophthalmia or microphthalmia were found. Conclusion Anophthalmia is more frequent than microphthalmia and is more often accompanied by FCA. Cleft lip and cleft palate are the most frequent concomitant malformations.